INSTITUTIONS AND FOREIGN DIRECT INVESTMENT: WHAT ROLE FOR INVESTMENT POLICY IN SOUTHEAST EUROPE? (The South East European Journal of Economics and Business, 2022)
Institutions are generally perceived as an important determinant of Foreign Direct Investment (FDI). Which institutions matter and why for FDI, remains however one of prominent questions in public policy debate amid complexities related to different institutional dimensions, and incomplete or even vague understanding of underlying mechanism(s) at work. In this paper we account for these ambiguities, and focus on institutions that reveal government efforts to design proper institutional and policy framework to attract FDI, as opposed to considering institutions in broader sense. Specifically, we contribute to FDI policy debate by analysing the impact of institutions measuring Investment policy and promotion on inward FDI flows in South East Europe (SEE). To this end we use a unique dataset that is comprised of specific, FDI related institutional indicators developed and published by the OECD. The results of this empirical investigation deeper our understanding on whether differences in FDI policies and institutional set-up across South East European (SEE) countries explain variations in inward FDI flows relaying on bilateral FDI flows and the gravity modelling technique. We bring novel evidence that investment policy efforts seemingly do pay off, highlighting the importance of progress and reforms embodied not only in FDI regulation, but also in FDI policy variables including FDI Promotion and Facilitation, Transparency, Privatisation policy and Public Private Partnership in attracting FDI in SEE. The analysed institutional effect properly accounts for the possible time-variant and context-dependant effect of institutions. The suggested importance of FDI policy variables seem valuable in terms of general FDI policy issues and trade-offs.